An accelerator neutron source target containing a multi-concentration anti-hydrogen embrittlement layer and a preparation method thereof

By using V-Ta composite material and magnetron cosputtering technology to form a multi-concentration V-Ta anti-hydrogen embrittlement layer, the brittle fracture problem caused by proton absorption of neutron source target is solved, and cracking or falling off of the anti-hydrogen embrittlement layer is avoided due to deposition stress, improving the stability and performance of the neutron source target.

CN118945971BActive Publication Date: 2025-03-07HUABORON NEUTRON TECH (HANGZHOU) CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411426020.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-14
Publication Date
2025-03-07
Estimated Expiration
2044-10-14

AI Technical Summary

Technical Problem

The existing neutron source targets are prone to brittle fracture due to proton absorption during use, and the single element anti-hydroembolization layer is prone to cracking or falling off due to deposition stress when the thickness increases.

Method used

The V-Ta composite material is used as the anti-hydrogen embrittlement layer, and the Ta content is controlled to increase from the matrix to the target layer through magnetron co-sputtering technology to increase within a specific range to form a multi-concentration V-Ta anti-hydrogen embrittlement layer.

Benefits of technology

Keep low stress when the hydrogen embrittlement layer is thick, effectively avoid cracking or falling off, and improve the stability and performance of the neutron source target.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118945971B_ABST
    Figure CN118945971B_ABST
Patent Text Reader

Abstract

The present invention relates to the field of neutron source targets, and discloses an accelerator neutron source target containing a multi-concentration anti-hydrogen embrittlement layer and a preparation method thereof. First, the multi-concentration V-Ta anti-hydrogen embrittlement layer of the accelerator neutron source of the present invention uses a V-Ta composite material as a raw material, and controls the Ta content to increase gradually from the substrate to the target layer in a specific range, so that the anti-hydrogen embrittlement layer can still have a lower stress when the anti-hydrogen embrittlement layer is thicker, thereby effectively avoiding the cracking or shedding of the anti-hydrogen embrittlement layer; secondly, the present invention constructs a multi-concentration V-Ta anti-hydrogen embrittlement layer with increasing Ta content by differentially setting the sputtering power. On this basis, the present invention also optimizes the disorder degree and phase structure of Ta and V atoms in the anti-hydrogen embrittlement layer of different thicknesses by the trolley rate, so as to obtain an anti-hydrogen embrittlement layer with better performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of neutron source targets, in particular to an accelerator neutron source target containing a multi-concentration anti-hydrogen embrittlement layer and a preparation method thereof. Background Art

[0002] Boron neutron capture therapy (BNCT) is a tumor treatment method in which a neutron source is used to introduce the boron-10 isotope into tumor cells. When the boron-10 is captured by neutrons, alpha particles and lithium nuclei are produced, which destroy the surrounding cancer cells. In BNCT, the neutron source usually comes from a neutron generator or a nuclear reactor. The choice and performance of the neutron source directly affect the treatment effect and safety. In recent years, accelerator-based neutron sources have become increasingly mature and have become the preferred neutron source in clinical practice.

[0003] Neutron source target is a component that produces neutrons. For accelerator neutron sources, the target that undergoes nuclear reactions and produces neutrons is one of the most critical and easily damaged components. Generally, the main nuclear reaction layer (i.e., target layer) is composed of lithium or beryllium. The target is usually required to withstand severe thermal mechanical, radiation, and hydrogen damage conditions, but the target is prone to brittle fracture due to the absorption of protons inside the metal during use.

[0004] In order to solve the above problems, a hydrogen embrittlement-resistant layer is usually provided between the substrate (usually Cu) and the target layer of the neutron source target. Vanadium (V) and tantalum (Ta) are important structural materials with good corrosion resistance and stability in high temperature and high pressure environments, and have a high hydrogen diffusion coefficient. They can be used as hydrogen embrittlement-resistant layers for neutron targets in accelerator boron neutron capture therapy (AB-BNCT). However, a single vanadium film needs to be 30μm thick to effectively prevent protons from entering the copper matrix, and a single tantalum film also needs to be 20μm thick to avoid proton deposition and hydrogen embrittlement.

[0005] At present, the main methods for preparing hydrogen embrittlement-resistant layers include vacuum plasma spraying (VPS), molten salt electroplating, chemical vapor deposition (CVD), physical vapor deposition (PVD) and magnetron sputtering. Among them, magnetron sputtering has the advantages of fast sputtering speed, dense film formation, excellent adhesion, and precise control of film formation. However, when using magnetron sputtering equipment to prepare single-element films, stress is easily deposited as the film thickness increases, resulting in cracking or falling off of the film. Summary of the invention

[0006] In order to solve the above technical problems, firstly, the present invention provides an accelerator neutron source target containing a multi-concentration anti-hydrogen embrittlement layer. The anti-hydrogen embrittlement layer in the accelerator neutron source target of the present invention uses V-Ta composite material as raw material, and controls the Ta content to increase gradually from the substrate to the target layer in a specific range, so that the anti-hydrogen embrittlement layer can still have a low stress when the anti-hydrogen embrittlement layer is thick, thereby effectively avoiding the cracking or shedding of the anti-hydrogen embrittlement layer; secondly, the present invention provides a preparation method for an accelerator neutron source target containing a multi-concentration V-Ta anti-hydrogen embrittlement layer. The present invention constructs a multi-concentration V-Ta anti-hydrogen embrittlement layer with increasing Ta content by differentially setting the sputtering power. On this basis, the present invention also optimizes the disorder degree and phase structure of Ta and V atoms in the anti-hydrogen embrittlement layer of different thicknesses by the trolley rate, so as to obtain a better performance anti-hydrogen embrittlement layer.

[0007] The specific technical scheme of the present invention is:

[0008] In the first aspect, the present invention provides an accelerator neutron source target containing a multi-concentration anti-hydrogen embrittlement layer, comprising: a substrate; a multi-concentration V-Ta anti-hydrogen embrittlement layer deposited on the surface of the substrate by magnetron co-sputtering technology; and a target material layer deposited on the surface of the multi-concentration V-Ta anti-hydrogen embrittlement layer. The Ta content of the multi-concentration V-Ta anti-hydrogen embrittlement layer increases gradually in the range of 10-100wt% (more preferably 20-90wt%) from the substrate to the target material layer.

[0009] In the prior art, the material of the hydrogen embrittlement-resistant layer is usually V or Ta. A single vanadium film or a single tantalum film needs to be thicker to effectively prevent protons from entering the substrate and avoid proton deposition and hydrogen embrittlement. The metal film formed by magnetron sputtering is prone to deposit stress when the film thickness is large, which may cause the film to crack or fall off.

[0010] To this end, the present invention has found through research that by using a V-Ta composite material as the anti-hydrogen embrittlement layer and controlling the Ta content to increase gradually from the substrate to the target layer within a specific range, the anti-hydrogen embrittlement layer can still have a lower stress when it is thicker, thereby effectively avoiding the cracking or falling off of the anti-hydrogen embrittlement layer.

[0011] The anti-hydrogen embrittlement layer of the present invention is obtained by a magnetron co-sputtering process. The difference between the thin film obtained by the magnetron co-sputtering process and the traditional single coating is that the atomic arrangement of the thin film is more chaotic. In the magnetron co-sputtering process, each element is interrupted by the second element before forming a continuous thin film. The higher the degree of chaos, the denser the atomic stacking, and the more grain boundaries formed. During the deposition process, the thin film can relax the strain by forming interfaces, dislocations or other defects, so the stress can also be better released.

[0012] Preferably, from the substrate to the target layer, the content of Ta in the multi-concentration V-Ta hydrogen embrittlement resistance layer increases linearly or in steps.

[0013] The Ta atomic layer transition in the linear increasing mode is uniform, but the power parameters of the two sputtering targets need to be precisely controlled during the preparation process, which makes the preparation difficult. The step-by-step increasing mode can effectively deal with the uneven distribution of protons in the anti-hydrogen embrittlement layer. A low Ta concentration is used in the proton deceleration zone, a medium Ta concentration is used in the proton large-scale distribution area, and a high Ta concentration is used in the proton blocking zone.

[0014] Preferably, the thickness of the multi-concentration V-Ta anti-hydrogen embrittlement layer is 15-40 microns (more preferably 15-30 microns).

[0015] The thickness of the multi-concentration V-Ta hydrogen embrittlement resistance layer of the present invention is comparable to that of the conventional hydrogen embrittlement resistance layer, but the stress of the hydrogen embrittlement resistance layer can be effectively reduced, thereby reducing the risk of cracking or falling off.

[0016] Further preferably, the multi-concentration V-Ta hydrogen embrittlement resistance layer is formed by stacking multiple layers of V-Ta films in a step-by-step manner.

[0017] Still further preferably, in a step-by-step manner, the multi-concentration V-Ta anti-hydrogen embrittlement layer is formed by stacking a low Ta concentration V-Ta film, a medium Ta concentration V-Ta film and a high Ta concentration V-Ta film; and the Ta contents in the low Ta concentration V-Ta film, the medium Ta concentration V-Ta film and the high Ta concentration V-Ta film are 10-30wt%, 30-60wt% and 60-90wt% respectively (further preferably 10-20wt%, 50-60wt%, 80-90wt%).

[0018] The present invention finds that, in a step-by-step manner, the multi-concentration V-Ta anti-hydrogen embrittlement layer is designed as a three-layer step-by-step structure, and the Ta concentrations in the three-layer films are limited to the above ranges, which has the best effect on reducing the stress of the anti-hydrogen embrittlement layer.

[0019] Still more preferably, the thickness of the low Ta concentration V-Ta film is 1-2 microns, the thickness of the medium Ta concentration V-Ta film is 10-15 microns, and the thickness of the high Ta concentration V-Ta film is 3-9 microns.

[0020] The present invention designs the thickness of the low concentration layer to be the thinnest, the medium concentration layer to be the thickest, and the high concentration layer to be in the middle because: when protons of a certain energy are injected into the target surface, their distribution in the anti-hydrogen embrittlement layer is uneven. The low concentration layer is the thinnest and can slow down the protons first, while the medium concentration layer is the thickest and can absorb and accommodate most of the protons, and the high concentration layer is in the middle to block the remaining protons from continuing to diffuse into the matrix.

[0021] Preferably, the substrate is made of copper.

[0022] Preferably, the target layer is made of lithium or beryllium.

[0023] In a second aspect, the present invention provides a method for preparing the above-mentioned accelerator neutron source target containing a multi-concentration hydrogen embrittlement resistance layer, wherein the content of Ta in the multi-concentration V-Ta hydrogen embrittlement resistance layer increases stepwise from the substrate to the target layer; the method for preparing the accelerator neutron source target comprises:

[0024] S1: Fix the Ta target and the V target on two target positions; fix the substrate on the mobile fixture trolley.

[0025] S2: The sputtering powers of the Ta target and the V target are adjusted to 50-100W and 100-300W respectively. Magnetron co-sputtering is performed in an inert atmosphere. The mobile fixture carriage is controlled to move back and forth between the Ta target and the V target at a rate of 10-15mm / s. After coating, a low Ta concentration V-Ta film is formed.

[0026] S3: The sputtering powers of the Ta target and the V target are adjusted to 100-300 W and 100-300 W respectively, and the trolley speed is 15-20 mm / s to form a V-Ta film with a medium Ta concentration.

[0027] S4: The sputtering powers of the Ta target and the V target are adjusted to 300-600W and 100-300W respectively, and the carriage speed is 20-25mm / s to form a high Ta concentration V-Ta film.

[0028] S5: depositing a target layer on the surface of the high Ta concentration V-Ta film.

[0029] The present invention uses magnetron co-sputtering to ionize an inert gas such as argon under the action of an electric field, and the ionized argon ions bombard the surfaces of the Ta target and the V target, and the target material sputters a large number of target material atoms and deposits them on the surface of the substrate. Specifically, in the above-mentioned magnetron co-sputtering process, the present invention mainly constructs a multi-concentration V-Ta hydrogen embrittlement resistance layer with a step-by-step increase in Ta content by differentially setting the sputtering power.

[0030] In addition, the present invention finds that the trolley rate has an important influence on the degree of disorder of Ta and V atoms in each layer of the film and the physical structure of the film. As mentioned above, the atomic arrangement in the film produced by the magnetron co-sputtering process is more chaotic. In the magnetron co-sputtering process, each element is interrupted by the second element before forming a continuous film. The higher the degree of disorder, the denser the atomic stacking, the more grain boundaries formed, and the better the stress release. Therefore, in theory, the higher the trolley rate, the higher the degree of disorder of Ta and V atoms.

[0031] The present invention sets the trolley rate of the low Ta concentration layer at the slowest (i.e., the lowest atomic disorder), the medium Ta concentration layer at the middle (i.e., the atomic disorder is middle), and the high Ta concentration layer at the fastest (i.e., the atomic disorder is highest) because: the trolley rate is set to the slowest in the low Ta concentration layer, so that the coating can be approximately regarded as alternating coating of two elements. This layer is connected to the substrate, and the multilayer film has a higher bonding force with the substrate than a single film; the medium Ta concentration layer trolley rate is set to the middle, because a large number of protons are distributed in this area, the atomic disorder is increased, more heterogeneous interfaces are provided, and a large number of hydrogen protons can be absorbed; and the high Ta concentration layer trolley rate is set to the fastest. When the film is deposited to a certain thickness, it is easily affected by stress and cracks, while the moving speed is higher, the atomic disorder is high, the grain boundary density is high, and thus the stress is small, and the film is not easy to crack.

[0032] In a third aspect, the present invention provides a method for preparing the above-mentioned accelerator neutron source target containing a multi-concentration hydrogen embrittlement resistance layer, wherein the content of Ta in the multi-concentration V-Ta hydrogen embrittlement resistance layer increases linearly from the substrate to the target layer; the method for preparing the accelerator neutron source target comprises:

[0033] S1: Install the Ta target and the V target on the two target positions of the magnetron sputtering coating machine respectively; fix the substrate on the mobile fixture trolley, pass inert gas into the sputtering chamber, and close the sputtering chamber.

[0034] S2: Adjust the initial sputtering power of the Ta target to 50-100W, the power increase rate to 50~100W / h, the initial sputtering power of the V target to 100-300W, the power increase rate to 20-50W / h, perform magnetron co-sputtering in an inert atmosphere, control the mobile fixture trolley to move back and forth between the Ta target and the V target at an initial rate of 10-15mm / s and an increase rate of 1.5-2.5mm / h, and after coating, a multi-concentration V-Ta anti-hydrogen embrittlement layer is formed.

[0035] S3: depositing a target layer on the surface of the multi-concentration V-Ta anti-hydrogen embrittlement layer.

[0036] Different from the step-by-step preparation process, when the Ta content in the hydrogen embrittlement-resistant layer increases linearly, the present invention correspondingly adopts the above-mentioned process of linearly increasing sputtering power and synchronously increasing trolley speed to construct a multi-concentration V-Ta hydrogen embrittlement-resistant layer.

[0037] Preferably, during magnetron co-sputtering, the gas pressure in the sputtering chamber is adjusted to 0.5-2 Pa, the duty cycle is 30-90%, and the bias voltage is -100V to -200V.

[0038] Preferably, the distance between the Ta target and the V target is 10-30 cm, and the distance between the Ta target and the sputtering chamber inlet is smaller than the distance between the V target and the sputtering chamber inlet.

[0039] Preferably, the reciprocating movement direction of the mobile fixture trolley is parallel to the straight line formed by the Ta target and the V target, and the spacing is 10-30 cm; the starting point and the end point of the reciprocating movement are flush with the Ta target and the V target respectively.

[0040] Compared with the prior art, the beneficial effects of the present invention are:

[0041] (1) The accelerator neutron source target of the present invention uses a V-Ta composite material as the anti-hydrogen embrittlement layer, and controls the Ta content to increase gradually from the substrate to the target layer within a specific range. It can still have a low stress when the anti-hydrogen embrittlement layer is thick, thereby effectively avoiding the cracking or shedding of the anti-hydrogen embrittlement layer.

[0042] (2) The present invention constructs a multi-concentration V-Ta hydrogen embrittlement-resistant layer on the substrate surface through a magnetron co-sputtering process. Compared with the traditional coating process, magnetron co-sputtering can obtain a hydrogen embrittlement-resistant layer with lower stress.

[0043] (3) The present invention constructs a multi-concentration V-Ta anti-hydrogen embrittlement layer with a step-by-step increase in Ta content by differentially setting the sputtering power. On this basis, the present invention also optimizes the disorder degree and phase structure of Ta and V atoms in the anti-hydrogen embrittlement layer of different thicknesses by the trolley rate, thereby facilitating the acquisition of an anti-hydrogen embrittlement layer with better performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0044] Figure 1 These are photos of copper sheets after magnetron co-sputtering coating in Examples 1-3 and Comparative Examples 1-3 (the first row from left to right are Examples 1-3, and the second row from left to right are Comparative Examples 1-3).

[0045] Figure 2 This is a SEM photo of the copper sheet after magnetron co-sputtering coating in Example 1.

[0046] Figure 3 This is the Ta element distribution diagram of the low Ta concentration V-Ta film in Example 1.

[0047] Figure 4 This is the V element distribution diagram of the low Ta concentration V-Ta film in Example 1.

[0048] Figure 5 This is the Ta element distribution diagram of the V-Ta film with medium Ta concentration in Example 1.

[0049] Figure 6 This is the V element distribution diagram of the V-Ta film with medium Ta concentration in Example 1.

[0050] Figure 7 This is the Ta element distribution diagram of the high Ta concentration V-Ta film in Example 1.

[0051] Figure 8 This is the V element distribution diagram of the high Ta concentration V-Ta film in Example 1.

[0052] Fig. 9 These are photos of the copper sheets after magnetron co-sputtering coating in Examples 4-7 (Examples 4-7 from left to right).

[0053] Fig.10 This is a SEM photograph of the copper sheet after magnetron co-sputtering coating in Example 4. DETAILED DESCRIPTION

[0054] The present invention will be further described below in conjunction with the embodiments.

[0055] Firstly, the present invention provides an accelerator neutron source target containing a multi-concentration anti-hydrogen embrittlement layer, which comprises: a substrate; a multi-concentration V-Ta anti-hydrogen embrittlement layer deposited on the surface of the substrate by magnetron co-sputtering technology; and a target material layer deposited on the surface of the multi-concentration V-Ta anti-hydrogen embrittlement layer.

[0056] The Ta content of the multi-concentration V-Ta anti-hydrogen embrittlement layer increases gradually from the substrate to the target layer in the range of 10-100wt% (more preferably 20-90wt%).

[0057] In some specific implementation cases, from the substrate to the target layer, the Ta content in the multi-concentration V-Ta anti-hydrogen embrittlement layer increases linearly or in steps.

[0058] In some specific implementation cases, the thickness of the multi-concentration V-Ta hydrogen embrittlement resistance layer is 15-40 microns (more preferably 15-30 microns).

[0059] In some more preferred implementation cases, the multi-concentration V-Ta anti-hydrogen embrittlement layer is formed by stacking multiple layers of V-Ta films in a step-by-step manner.

[0060] In some more preferred implementation cases, the multi-concentration V-Ta anti-hydrogen embrittlement layer is formed by stacking a low Ta concentration V-Ta film, a medium Ta concentration V-Ta film and a high Ta concentration V-Ta film in a step-by-step manner; and the Ta contents in the low Ta concentration V-Ta film, the medium Ta concentration V-Ta film and the high Ta concentration V-Ta film are 10-30wt%, 30-60wt% and 60-90wt% (further preferably 10-20wt%, 50-60wt% and 80-90wt%) respectively.

[0061] In some more preferred implementation cases, the thickness of the low Ta concentration V-Ta film is 1-2 microns, the thickness of the medium Ta concentration V-Ta film is 10-15 microns, and the thickness of the high Ta concentration V-Ta film is 3-9 microns.

[0062] In some specific implementation cases, the substrate is made of copper.

[0063] In some specific implementation cases, the target layer is made of lithium or beryllium.

[0064] In a second aspect, the present invention provides a method for preparing an accelerator neutron source target containing a multi-concentration anti-hydrogen embrittlement layer, wherein the Ta content in the multi-concentration V-Ta anti-hydrogen embrittlement layer of the accelerator neutron source target increases in a step-by-step manner from the substrate to the target material layer.

[0065] The preparation method of the accelerator neutron source target specifically includes:

[0066] S1: Install the Ta target and the V target on the two target positions of the magnetron sputtering coating machine respectively; fix the substrate on the mobile fixture trolley, pass inert gas into the sputtering chamber, and close the sputtering chamber.

[0067] S2: The sputtering powers of the Ta target and the V target are adjusted to 50-100W and 100-300W respectively. Magnetron co-sputtering is performed in an inert atmosphere. The mobile fixture carriage is controlled to move back and forth between the Ta target and the V target at a rate of 10-15mm / s. After coating, a low Ta concentration V-Ta film is formed.

[0068] S3: The sputtering powers of the Ta target and the V target are adjusted to 100-300 W and 100-300 W respectively, and the trolley speed is 15-20 mm / s to form a V-Ta film with a medium Ta concentration.

[0069] S4: The sputtering powers of the Ta target and the V target are adjusted to 300-600W and 100-300W respectively, and the carriage speed is 20-25mm / s to form a high Ta concentration V-Ta film.

[0070] S5: depositing a target layer on the surface of the high Ta concentration V-Ta film.

[0071] In the third aspect, the present invention provides a method for preparing an accelerator neutron source target containing a multi-concentration anti-hydrogen embrittlement layer, in which the Ta content in the multi-concentration V-Ta anti-hydrogen embrittlement layer increases linearly from the substrate to the target material layer.

[0072] The preparation method of the accelerator neutron source target specifically includes:

[0073] S1: Install the Ta target and the V target on the two target positions of the magnetron sputtering coating machine respectively; fix the substrate on the mobile fixture trolley, pass inert gas into the sputtering chamber, and close the sputtering chamber.

[0074] S2: Adjust the initial sputtering power of the Ta target to 50-100W, the power increase rate to 50~100W / h, the initial sputtering power of the V target to 100-300W, the power increase rate to 20-50W / h, perform magnetron co-sputtering in an inert atmosphere, control the mobile fixture trolley to move back and forth between the Ta target and the V target at an initial rate of 10-15mm / s and an increase rate of 1.5-2.5mm / h, and after coating, a multi-concentration V-Ta anti-hydrogen embrittlement layer is formed.

[0075] S3: depositing a target layer on the surface of the multi-concentration V-Ta anti-hydrogen embrittlement layer.

[0076] In some specific implementation cases, during magnetron co-sputtering, the gas pressure in the sputtering chamber is adjusted to 0.5-2Pa, the duty cycle is 30-90%, and the bias voltage is -100V to -200V.

[0077] In some specific implementation cases, the distance between the Ta target and the V target is 10-30 cm, and the distance between the Ta target and the sputtering chamber inlet is smaller than the distance between the V target and the sputtering chamber inlet.

[0078] In some specific implementation cases, the reciprocating movement direction of the mobile fixture trolley is parallel to the straight line formed by the Ta target and the V target, and the spacing is 10-30 cm; the starting point and the end point of the reciprocating movement are flush with the Ta target and the V target respectively.

[0079] Specific Examples and Comparative Examples

[0080] (A) The Ta content in multi-concentration V-Ta anti-hydrogen embrittlement layer increases in steps.

[0081] Example 1

[0082] An accelerator neutron source target containing a multi-concentration V-Ta anti-hydrogen embrittlement layer, comprising: a substrate; a multi-concentration V-Ta anti-hydrogen embrittlement layer deposited on the surface of the substrate; and a target material layer deposited on the surface of the multi-concentration V-Ta anti-hydrogen embrittlement layer. The multi-concentration V-Ta anti-hydrogen embrittlement layer is formed by stacking a low Ta concentration V-Ta film, a medium Ta concentration V-Ta film, and a high Ta concentration V-Ta film. Specifically, the Ta contents in the low Ta concentration V-Ta film, the medium Ta concentration V-Ta film, and the high Ta concentration V-Ta film are 15wt%, 50wt%, and 80wt%, respectively, and the thicknesses are 2 microns, 14 microns, and 5 microns, respectively.

[0083] The method for preparing the accelerator neutron source target containing a multi-concentration V-Ta hydrogen embrittlement-resistant layer specifically comprises:

[0084] (1) Substrate surface pretreatment: A copper sheet with a diameter of 12.5 mm and a thickness of 1 mm was used as the substrate. It was polished with 80-grit sandpaper for 5 min, and then further polished with 200-grit and 400-grit sandpaper for 5 min each. Finally, the substrate was cleaned with acetone, alcohol, and ultrapure water for 5 min each, and then dried in a vacuum drying oven for 1 h.

[0085] (2) Installation: The Ta target and the Ti target are installed on the two target positions of the magnetron sputtering coating machine respectively (the distance between the Ta target and the Ti target is 20 cm, and the distance between the Ta target and the Ti target and the sampling port of the sputtering chamber are 50 cm and 70 cm respectively); the substrate is attached to the stainless steel plate and fixed on the mobile fixture trolley (the direction of the trolley's reciprocating movement is parallel to the straight line formed by the Ta target and the Ti target, and the distance between them is 20 cm; the starting point and end point of the reciprocating movement are flush with the Ta target and the Ti target respectively).

[0086] (3) Pre-sputtering: Close the sputtering chamber and evacuate the chamber to a pressure of ≥5×10 -4 Pa, and then argon gas was introduced for pre-sputtering for 5 min.

[0087] (4) Co-sputtering: Magnetron co-sputtering is performed, and the condition parameters of each stage are set as follows:

[0088] (4.1) The duty cycle is 80%, the bias voltage is -150V, the sputtering pressure is 0.5Pa, the sputtering power of the Ta target and the V target is adjusted to 50W and 300W respectively, and the mobile fixture carriage is controlled to move back and forth between the Ta target and the V target at a rate of 10mm / s. After coating, a low Ta concentration V-Ta film is formed (the element distribution diagram is shown in Figure 3-4 as shown).

[0089] (4.2) Keeping other conditions unchanged, the sputtering powers of Ta target and V target were adjusted to 150 W and 150 W respectively, and the trolley speed was 15 mm / s to form a V-Ta film with medium Ta concentration (element distribution diagram as shown in Figure 5-6 as shown).

[0090] (4.2) Keeping other conditions unchanged, the sputtering powers of Ta target and V target were adjusted to 600W and 100W respectively, and the carriage speed was 25mm / s to form a high Ta concentration V-Ta film (SEM photo as shown in Figure 2 The element distribution diagram is shown in Figure 7-8 as shown).

[0091] (5) A target material layer is deposited on the surface of a high Ta concentration V-Ta film to produce an accelerator neutron source target.

[0092] Example 2

[0093] Compared with Example 1, the only difference between Example 2 is that in the final multi-concentration V-Ta anti-hydrogen embrittlement layer, the thickness of the low Ta concentration V-Ta film, the medium Ta concentration V-Ta film and the high Ta concentration V-Ta film are the same, all of which are 7 microns (the total thickness of the three layers is the same as that of Example 1).

[0094] Example 3

[0095] The only difference between Example 3 and Example 1 is that during the magnetron co-sputtering in step (4), the moving speed of the carriage is a constant speed of 20 mm / s.

[0096] Comparative Example 1

[0097] The only difference between Comparative Example 1 and Example 1 is that the contents of V and Ta in the V-Ta hydrogen embrittlement-resistant layer are fixed at 50% and 50%, respectively, that is, the ratio of V to Ta in the thickness direction remains unchanged. The magnetron co-sputtering process conditions of Comparative Example 1 are as follows:

[0098] The sputtering powers of the Ta target and the V target were 150 W and 150 W respectively, the duty cycle was 80%, the bias voltage was -150 V, the sputtering gas pressure was 0.5 Pa, the carriage speed was 15 mm / s, and a V-Ta hydrogen embrittlement-resistant layer with a thickness of 21 microns was prepared.

[0099] Comparative Example 2

[0100] Compared with Example 1, Comparative Example 2 is different in that the anti-hydrogen embrittlement layer is a pure Ta film with the same thickness as Example 1. The magnetron co-sputtering process conditions of Comparative Example 2 are as follows:

[0101] The sputtering power of the Ta target was 300 W, the duty cycle was 80%, the bias voltage was -150 V, the sputtering gas pressure was 0.5 Pa, and the carriage speed was 0 mm / s, and a Ta hydrogen embrittlement-resistant layer with a thickness of 21 microns was prepared.

[0102] Comparative Example 3

[0103] Compared with Example 1, Comparative Example 3 is different in that the anti-hydrogen embrittlement layer is a pure V film with the same thickness as Example 1. The magnetron co-sputtering process conditions of Comparative Example 3 are as follows:

[0104] The sputtering power of the V target was 300 W, the duty cycle was 80%, the bias voltage was -150 V, the sputtering gas pressure was 0.5 Pa, and the carriage speed was 0 mm / s, and a V anti-hydrogen embrittlement layer with a thickness of 21 microns was prepared.

[0105] Performance Analysis

[0106] The performance test of the anti-hydrogen embrittlement layer constructed by the above embodiments and comparative examples is performed, and the performance test results are shown in the following table:

[0107]

[0108] It can be seen from the data in the above table that the samples obtained in Examples 1-3 have significantly lower film stress and better coating effect than the samples obtained in Comparative Examples 1-3. Specifically:

[0109] The only difference between Comparative Example 1 and Example 1 is that the contents of V and Ta in the V-Ta hydrogen embrittlement resistance layer are fixed at 50% and 50%, respectively, that is, the ratio of V and Ta in the thickness direction remains unchanged. The results show that the film stress of the obtained sample is significantly higher than that of Example 1, and a small amount of cracking occurs in the film after coating.

[0110] The difference between Comparative Example 2 and Example 1 is that the anti-hydrogen embrittlement layer is a pure Ta film with the same thickness as Example 1. The results show that the film stress of the obtained sample is also significantly higher than that of Example 1, or even worse than that of Comparative Example 1, and large-area cracking occurs in the film after coating.

[0111] Compared with Example 1, Comparative Example 3 is different in that the anti-hydrogen embrittlement layer is a pure V film with the same thickness as Example 1. The results show that similar to Comparative Example 2, the film stress of the obtained sample is also significantly higher than that of Example 1, while inferior to that of Comparative Example 1, and the film also has large-area cracking after coating.

[0112] Compared with Example 1, Example 2 differs only in that the thickness of the low Ta concentration V-Ta film, the medium Ta concentration V-Ta film and the high Ta concentration V-Ta film in the final multi-concentration V-Ta anti-hydrogen embrittlement layer is the same, which is 7 microns (the total thickness of the three layers is the same as that of Example 1). The results show that although the film stress of the sample obtained in Example 2 is better than that of Comparative Examples 1-3, it is lower than that of Example 1, indicating that further optimization of the thickness of the three layers of film in the anti-hydrogen embrittlement layer can further reduce the film stress and improve the coating effect.

[0113] The only difference between Example 3 and Example 1 is that during the magnetron co-sputtering in step (4), the moving speed of the trolley is a constant speed of 20 mm / s. The results show that although the film stress of the sample obtained in Example 3 is better than that of Comparative Examples 1-3 and Example 2, it is also lower than that of Example 1, indicating that the targeted and differentiated design of the moving speed of the trolley for the three-layer film in the anti-hydrogen embrittlement layer during the magnetron co-sputtering process can be further optimized to further reduce the film stress and improve the coating effect.

[0114] (ii) The Ta content in multi-concentration V-Ta anti-hydrogen embrittlement layer increases linearly.

[0115] Example 4

[0116] An accelerator neutron source target containing a multi-concentration V-Ta anti-hydrogen embrittlement layer, comprising: a substrate; a multi-concentration V-Ta anti-hydrogen embrittlement layer deposited on the surface of the substrate; and a target material layer deposited on the surface of the multi-concentration V-Ta anti-hydrogen embrittlement layer. The multi-concentration V-Ta anti-hydrogen embrittlement layer has a Ta content that increases linearly from 20wt% to 90wt% from the substrate to the target material layer, and the total thickness of the anti-hydrogen embrittlement layer is 21 microns (same as in Example 1).

[0117] The method for preparing the accelerator neutron source target containing a multi-concentration V-Ta hydrogen embrittlement-resistant layer specifically comprises:

[0118] (1) Substrate surface pretreatment: A copper sheet with a diameter of 12.5 mm and a thickness of 1 mm was used as the substrate. It was polished with 80-grit sandpaper for 5 min, and then further polished with 200-grit and 400-grit sandpaper for 5 min each. Finally, the substrate was cleaned with acetone, alcohol, and ultrapure water for 5 min each, and then dried in a vacuum drying oven for 1 h.

[0119] (2) Installation: The Ta target and the Ti target are installed on the two target positions of the magnetron sputtering coating machine respectively (the distance between the Ta target and the Ti target is 20 cm, and the distance between the Ta target and the Ti target and the sampling port of the sputtering chamber are 50 cm and 70 cm respectively); the substrate is attached to the stainless steel plate and fixed on the mobile fixture trolley (the direction of the trolley's reciprocating movement is parallel to the straight line formed by the Ta target and the Ti target, and the distance between them is 20 cm; the starting point and end point of the reciprocating movement are flush with the Ta target and the Ti target respectively).

[0120] (3) Pre-sputtering: Close the sputtering chamber and evacuate the chamber to a pressure of ≥5×10 -4 Pa, and then argon gas was introduced for pre-sputtering for 5 min.

[0121] (4) Co-sputtering: Magnetron co-sputtering is performed, and the condition parameters of each stage are set as follows:

[0122] (4.1) The duty cycle was adjusted to 80%, the bias voltage was -150 V, and the sputtering pressure was 0.5 Pa. The initial sputtering power of the Ta target was adjusted to 50 W, the power increase rate was 60 W / h, and the initial sputtering power of the V target was adjusted to 150 W, the power increase rate was 30 W / h. Magnetron co-sputtering was performed in an inert atmosphere. The mobile fixture carriage was controlled to move back and forth between the Ta target and the V target at an initial speed of 10 mm / s and a speed increase of 2 mm / h. After coating, a multi-concentration V-Ta hydrogen embrittlement-resistant layer was formed (SEM photos are shown in Figure 2). Fig.10 as shown).

[0123] (5) A target material layer is deposited on the surface of a multi-concentration V-Ta hydrogen embrittlement resistance layer to produce an accelerator neutron source target.

[0124] Example 5

[0125] The only difference between Example 5 and Example 4 is that during the magnetron co-sputtering in step (4), the moving speed of the carriage is a constant speed of 5 mm / s.

[0126] Example 6

[0127] The only difference between Example 6 and Example 4 is that during the magnetron co-sputtering in step (4), the moving speed of the carriage is a constant speed of 20 mm / s.

[0128] Example 7

[0129] The only difference between Example 7 and Example 4 is that during the magnetron co-sputtering in step (4), the moving speed of the carriage is a constant speed of 30 mm / s.

[0130] Performance Analysis

[0131] The performance test of the anti-hydrogen embrittlement layer constructed in the above embodiments is performed, and the performance test results are shown in the following table:

[0132]

[0133] From the data in the above table, it can be seen that the Ta content in the multi-concentration V-Ta hydrogen embrittlement resistance layer of Examples 4-7 increases linearly, and the data of the obtained samples show that the film stress is generally lower (lower than that of Comparative Example 1), and the coating effect is relatively better. Specifically:

[0134] The only difference between Example 5 and Example 4 is that during the magnetron co-sputtering in step (4), the moving speed of the carriage is a constant speed of 5 mm / s. The results show that the film stress of the obtained sample is significantly higher than that of Example 4, and the coating is relatively poor. This indicates that the moving speed of the carriage in Example 5 is too slow and is not within the optimal range.

[0135] The only difference between Example 6 and Example 4 is that during the magnetron co-sputtering in step (4), the trolley moving speed is a constant speed of 20 mm / s. The results show that although the film stress of the sample obtained in Example 6 is better than that in Example 5, it is significantly higher than that in Example 4, and the coating is relatively poor. This shows that in the process of magnetron co-sputtering, by optimizing the trolley moving speed in a targeted and real-time manner, the film stress can be further reduced and the coating effect can be improved.

[0136] The only difference between Example 7 and Example 1 is that during the magnetron co-sputtering in step (4), the moving speed of the carriage is a constant speed of 30 mm / s. Similar to Example 6, the results show that the film stress of the sample obtained in Example 7 is better than that in Example 5, but also lower than that in Example 1, indicating that further optimization of the thickness of the three-layer film in the anti-hydrogen embrittlement layer can further reduce the film stress and improve the coating effect.

[0137] The raw materials and equipment used in the present invention, unless otherwise specified, are all commonly used raw materials and equipment in the art; the methods used in the present invention, unless otherwise specified, are all conventional methods in the art.

[0138] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent transformation made to the above embodiment based on the technical essence of the present invention still falls within the protection scope of the technical solution of the present invention.

Claims

1. A method for preparing an accelerator neutron source target containing a multi-concentration anti-hydrogen embrittlement layer comprises: S1: Fix the Ta target and V target on the target position; fix the substrate on the trolley; S2: Adjust the initial sputtering power of the Ta target to 50-100W, the power increase rate to 50-100W / h, the initial sputtering power of the V target to 100-300W, the power increase rate to 20-50W / h, perform magnetron co-sputtering in an inert atmosphere, and control the trolley to move back and forth between the Ta target and the V target at an initial rate of 10-15mm / s and an increase rate of 1.5-2.5mm / h to form a multi-concentration V-Ta hydrogen embrittlement resistance layer; S3: depositing a target layer on the surface of the multi-concentration V-Ta anti-hydrogen embrittlement layer; The obtained accelerator neutron source target comprises: a substrate, a multi-concentration V-Ta hydrogen embrittlement resistance layer and a target material layer; In the multi-concentration V-Ta anti-hydrogen embrittlement layer, the Ta content increases linearly in the range of 10-100wt% from the substrate to the target layer.

2. The preparation method according to claim 1, characterized in that: The thickness of the multi-concentration V-Ta hydrogen embrittlement resistance layer is 15-40 microns.

3. A method for preparing an accelerator neutron source target containing a multi-concentration anti-hydrogen embrittlement layer, characterized in that include: S1: Fix the Ta target and V target on the target position; fix the substrate on the trolley; S2: The sputtering powers of the Ta target and the V target are adjusted to 50-100W and 100-300W respectively, and magnetron co-sputtering is performed in an inert atmosphere. The trolley is controlled to move back and forth between the Ta target and the V target at a rate of 10-15mm / s to form a low Ta concentration V-Ta film; S3: adjusting the sputtering powers of the Ta target and the V target to 100-300W and 100-300W respectively, and the trolley speed to 15-20mm / s, to form a V-Ta film with a medium Ta concentration; S4: adjusting the sputtering power of the Ta target and the V target to 300-600W and 100-300W respectively, and the carriage speed to 20-25mm / s, to form a V-Ta film with a high Ta concentration; S5: depositing a target layer on the surface of the high Ta concentration V-Ta film; The obtained accelerator neutron source target comprises: a substrate, a multi-concentration V-Ta hydrogen embrittlement resistance layer and a target material layer; In the multi-concentration V-Ta anti-hydrogen embrittlement layer, the Ta content increases step by step in the range of 10-100wt% from the substrate to the target layer.

4. The preparation method according to claim 3, characterized in that: The thickness of the multi-concentration V-Ta hydrogen embrittlement resistance layer is 15-40 microns.

5. The preparation method according to claim 3, characterized in that: The multi-concentration V-Ta anti-hydrogen embrittlement layer is formed by stacking a low Ta concentration V-Ta film, a medium Ta concentration V-Ta film and a high Ta concentration V-Ta film in a step-by-step manner; and the Ta contents in the low Ta concentration V-Ta film, the medium Ta concentration V-Ta film and the high Ta concentration V-Ta film are 10-30wt%, 30-60wt% and 60-90wt% respectively.

6. The preparation method according to claim 5, characterized in that: The thickness of the low Ta concentration V-Ta film is 1-2 microns, the thickness of the medium Ta concentration V-Ta film is 10-15 microns, and the thickness of the high Ta concentration V-Ta film is 3-9 microns.

7. The preparation method according to claim 1 or 3, characterized in that: The material of the substrate is copper; and / or The target layer is made of lithium or beryllium.

8. The preparation method according to claim 1 or 3, characterized in that: During magnetron co-sputtering, the gas pressure in the sputtering chamber was adjusted to 0.5-2Pa, the duty cycle was 30-90%, and the bias voltage was -100V to -200V.

9. The preparation method according to claim 1 or 3, characterized in that: The distance between the Ta target and the V target is 10-30 cm, and the distance between the Ta target and the injection port of the sputtering chamber is smaller than the distance between the V target and the injection port of the sputtering chamber.

10. The preparation method according to claim 1 or 3, characterized in that: The reciprocating movement direction of the trolley is parallel to the straight line formed by the Ta target and the V target, and the spacing is 10-30 cm; the starting point and the end point of the reciprocating movement are flush with the Ta target and the V target respectively.

Citation Information

Patent Citations

  • High-binding-force multi-gradient target system and preparation method thereof

    CN118450586A